การประเมินคุณภาพวิทยานิพนธ์ของนิสิตระดับดุษฎีบัณฑิต มหาวิทยาลัยนเรศวร - บัวสนธ์ รัตนะ; หลินเจริญ เอื้อมพร; ศรีพิมาย พิจิกานต์; จิตรโคตร ปริญญา; สุขสำราญ ประสิตา; ภู่สวาสดิ์ ปัทมา; จันทรคีรี สุภาพร (Journal of Education and Innovation, 2014)
บทคัดย่อ การวิจัยครั้งนี้ มีวัตถุประสงค์เพื่อ 1) สำรวจวิทยานิพนธ์ของนิสิตระดับดุษฎีบัณฑิต ในมหาวิทยาลัยนเรศวรที่สำเร็จการศึกษาในช่วงปี พ.ศ. 2550 – 2554 2) ประเมินคุณภาพวิทยานิพนธ์ของนิสิตระดับดุษฎีบัณฑิต ในมหาวิทยาลัยนเรศวรที่สำเร็จการศึกษาในช่วงปี พ.ศ. 2550 – 2554 กลุ่มตัวอย่างเป็นวิทยานิพนธ์ของนิสิตระดับดุษฎีบัณฑิต ในมหาวิทยาลัยนเรศวรที่สำเร็จการศึกษาในช่วงปี พ.ศ. 2550 – 2554 ซึ่งผู้วิจัยได้กำหนดขนาดกลุ่มตัวอย่างวิทยานิพนธ์ของนิสิตที่จะใช้ในการประเมินคุณภาพวิทยานิพนธ์ในครั้งนี้ จำนวน 30 เล่ม ทำการสุ่มแบบแบ่งชั้นจำแนกตามคณะแบบสัดส่วนกลุ่มตัวอย่างในแต่ละคณะ จากนั้นทำการสุ่มอย่างง่ายด้วยวิธีการจับสลากตามรายชื่อวิทยานิพนธ์ ทำการเก็บรวบรวมข้อมูลโดยใช้แบบประเมินคุณภาพวิทยานิพนธ์ ที่ผู้วิจัยสร้างขึ้น มีจำนวนทั้งสิ้น 10 ด้าน 29 ประเด็น นำข้อมูลที่ได้มาทำการวิเคราะห์ข้อมูลด้วยโปรแกรมสำเร็จรูปทางสถิติ คำนวณหาค่าร้อยละ ค่าเฉลี่ย ส่วนเบี่ยงเบนมาตรฐาน ค่าสหสัมพันธ์เพียร์สัน ผลการวิจัยสรุปได้ดังนี้ 1. ผลการสำรวจวิทยานิพนธ์ มหาวิทยาลัยนเรศวรที่สำเร็จการศึกษา ในช่วงปี พ.ศ. 2550 – 2554 พบว่า จำนวนวิทยานิพนธ์ของนิสิตระดับดุษฎีบัณฑิตมหาวิทยาลัยนเรศวรที่สำเร็จการศึกษา ในช่วงปี พ.ศ. 2550 – 2554 เมื่อจำแนกตามคณะ เรียงลำดับจากมากไปหาน้อย 3 ลำดับแรก พบว่า คณะศึกษาศาสตร์ คณะสังคมศาสตร์ และคณะวิทยาศาสตร์ ตามลำดับ ส่วนคณะที่มีวิทยานิพนธ์ของนิสิตระดับปริญญาดุษฎีบัณฑิตสำเร็จการศึกษาน้อยที่สุดคือ คณะเกษตรศาสตร์ 2. ผลการประเมินคุณภาพวิทยานิพนธ์นิสิตระดับดุษฎีบัณฑิต ในมหาวิทยาลัยนเรศวรที่สำเร็จการศึกษาในช่วงปีพ.ศ. 2550-2554 2.1 จำแนกตามประเด็นการประเมินใน 29 ประเด็น พบว่ามีประเด็นการประเมินอยู่ในระดับดีมาก 24 ประเด็น ซึ่ง 3 ลำดับแรก คือ กระบวนการเก็บรวบรวมข้อมูลเหมาะสมกับปัญหาการวิจัย รองลงมาคือ ผลสรุปที่ได้จากการวิจัยมีความครอบคลุม และสอดคล้องกับวัตถุประสงค์/ปัญหาวิจัย และวัตถุประสงค์การวิจัยสอดคล้องกับชื่อเรื่องและปัญหาการวิจัย ประเด็นที่ระดับผลการประเมินอยู่ในระดับต่ำ คือ สมมุติฐานการวิจัยมีความเหมาะสม ชัดเจน และสมเหตุสมผล 2.2 ผลการประเมินคุณภาพวิทยานิพนธ์ของนิสิตระดับปริญญาดุษฎีบัณฑิตในมหาวิทยาลัยนเรศวรที่ทำเสร็จแล้วในช่วง ปี พ.ศ. 2550 - 2554 พบว่า ในภาพรวมอยู่ในระดับดีมาก เมื่อแยกเป็นรายด้านแล้วพบว่า ด้านที่มีคะแนนผลการประเมินมากที่สุด คือด้านความเป็นมาและความสำคัญของปัญหา และด้านสาระในภาคผนวก รองลงมาคือด้านวิธีดำเนินการวิจัย ส่วนด้านที่มีคะแนนผลการประเมินน้อยที่สุดคือด้านการกำหนดกรอบความคิดในการวิจัย คำสำคัญ: ประเมินคุณภาพวิทยานิพนธ์ Abstract The purposes of this research were to 1) survey the thesis of doctoral program students, Naresuan University, who graduated between B.E. 2550 – 2554, 2) evaluate the thesis quality of doctoral program students, Naresuan University, who graduated between B.E. 2550 – 2554. The sample group was the thesis of doctoral program students, Naresuan University, who graduated between B.E. 2550 – 2554. The researcher determined the size of sample thesis used for the 30 theses quality evaluation. The random sampling was used in terms of categorization according to the faculty through sample group proportion in each faculty; then the simple random sampling was carried out by lot according to the name lists of thesis method. The data collection was done by using the model of thesis quality evaluation created by the researcher. The model consisted of 10 aspects and 29 issues. The data was analyzed by statistical packages, percentage, mean, standard deviation, and Pearson Correlation Coefficient. The research results could be concluded as follows: 1. Thesis survey results in Naresuan University of graduation between B.E. 2550 – 2554 was found that the thesis numbers of doctoral program students, Naresuan University, who graduated between B.E. 2550–2554 when categorized by faculty ranked from the most to least at the first 3 levels, it included the Faculty of Education, Faculty of Social Sciences, and Faculty of Science, respectively. Whereas the faculty which had the thesis of doctoral program students who graduated the least was the Faculty of Agriculture. 2. The results of thesis quality evaluation on the doctoral program students, Naresuan University, who graduated between B.E. 2550 – 2554 included as follows: 2.1 When categorized by 29 evaluation issues, it was found that the issues evaluated at the very good level was 24 issues, the first 3 levels included the process of data collection was appropriate for the research problems; secondly, the research was comprehensive, and in accordance with the objectives/research problems; thirdly, the research objectives were in accordance with the title and research problems. For the issues which evaluation result level was low included the research hypothesis was appropriate, clear and valid. 2.2 The results of thesis quality evaluation of doctoral program students, Naresuan University, which was completed between B.E. 2550–2554 was found that as overall image was at the very good level. When categorized in each aspect, the aspects which had the highest scores of evaluation results were the backgrounds and importance of problems, and content aspects in the index section; secondly, the research methodology, whereas the aspect of having the scores of evaluation results the least was in terms of the determination on conceptual framework in the research. Key word: thesis quality evaluation